Male mammary gland development after apatinib therapy in advanced gastric cancer: A case report. Issue 28 (10th July 2020) - Hui, Yan; Wang, Jingchun; Han, Jianguo; Guo, Zhifeng; Sun, Siqi; Wu, Zifang; Wang, Yanqiu; Han, Zhimin; Chen, Xiangbin
Abstract: Rationale: Most gastric cancer patients are diagnosed at mid- to late-stage and lose the chance of radical surgery, medical treatment is especially important to prolong the survival of patients. Apatinib mesylate, which is a small molecule vascular endothelial growth factor receptor 2 tyrosine kinase inhibitor, could be used as antiangiogenesis therapy for gastric cancer. Patient concerns: A 67-year-old man sought medical care for upper abdominal discomfort. Diagnosis: The patient was diagnosed as mixed medullary differentiated gastric adenocarcinoma, and immunohistochemistry suggested HER-2 (2+). Interventions: The patient received chemotherapy consisting of oxaliplatin combined with S-1 as first-line treatment, and targeted therapy with apatinib mesylate as second-line treatment. Outcomes: After 4 months of first-line chemotherapy, the patient received apatinib treatment immediately at a dose of 500 mg/d orally and died of cardiac arrest with 8.5 months of overall survival. During this period of targeted therapy with apatinib mesylate, this male patient suffered mammary gland development besides other common adverse reactions. Lessons: This case report is the first to report the case of male mammary gland development after oral apatinib.